Visual Scaffolding in Discovery Learning: Reducing Cognitive Load to Enhance Mastery of Abstract Biological Concepts - Tirta Rohmatain Solikah; Dyah Astriani; Phurkonni Musor (Jurnal Pendidikan Progresif, 2026)
The complexity of physiological processes in the digestive system often poses significant cognitive challenges for junior high school students, leading to suboptimal conceptual mastery. Conventional learning materials often lack the visual scaffolding needed to help students organize abstract concepts. This study aims to develop Visual Mind Map Worksheets integrated with the Discovery Learning model and to analyze their validity, practicality, and effectiveness in improving students' understanding of science concepts. This research utilized a Research and Development (R&D) design following the 4-D model (Define, Design, Develop, and Disseminate). The trial sample consisted of 28 eighth-grade students at Asa Cendekia Junior High School, selected using purposive sampling. Data were collected using expert validation sheets, learning implementation observation rubrics, and a written test measuring cognitive levels C2 (Understanding), C3 (Applying), and C4 (Analyzing). The data were analyzed using descriptive statistics, paired sample t-tests, and N-gain scores. The results indicated that the developed product met the criteria for high feasibility. Expert validation yielded an average score of 3.90 (Very Valid), while the practicality test showed a 98% implementation rate of learning activities (Very Practical). Statistical analysis revealed a significant difference between pretest and posttest scores (p = 0.000 < 0.05). Furthermore, the N-gain analysis demonstrated an improvement in the "Medium" category across all indicators, with a hierarchical achievement pattern: Understanding (0.635), Applying (0.416), and Analyzing (0.444). These findings conclude that the Visual Mind Map Worksheet is a feasible and effective instructional tool. By leveraging visual organization, the worksheet acts as a cognitive scaffold that helps students reconstruct complex biological information into a coherent understanding. Keywords: visual mind map-based worksheets, discovery learning, science concept understanding, digestive system.